2021
DOI: 10.1177/15569845211030917
|View full text |Cite
|
Sign up to set email alerts
|

500 Consecutive Robotic Lobectomies for Non-Small Cell Lung Cancer: Perioperative and Oncologic Outcomes

Abstract: Objective Clinical adoption of robotic lobectomy for management of lung cancer is rapidly increasing across the world. Several studies have evaluated the technique with regards to perioperative and cost outcomes, with evidence beginning to grow regarding long-term oncologic outcomes. We report perioperative and oncologic outcomes in our single institution experience with 500 consecutive robotic lobectomies, including a significant portion for locally advanced disease. Methods This study is a retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Earlier diagnosis leads to a survival gain of 33% and 60% for regional and local cancer stages, respectively ( 3 ). Surgery is the mainstay treatment for early stage NSCLC ( 4 ); however, treatment failure in patients undergoing surgery for early stage NSCLC is quite high (30–55%) ( 5 ). Treatment failure may result in locoregional recurrence and distant metastasis and is the most common cause of death in patients with lung cancer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier diagnosis leads to a survival gain of 33% and 60% for regional and local cancer stages, respectively ( 3 ). Surgery is the mainstay treatment for early stage NSCLC ( 4 ); however, treatment failure in patients undergoing surgery for early stage NSCLC is quite high (30–55%) ( 5 ). Treatment failure may result in locoregional recurrence and distant metastasis and is the most common cause of death in patients with lung cancer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure4 Aalen-Johansen estimates of transition probabilities from surgery to surgery, locoregional recurrence, distant metastasis or death in a stacked display format.…”
mentioning
confidence: 99%
“…Nevertheless, conversion rate remains < 10% in recent series, thus at least not higher than VATS [ 37 ]. Reasons for conversion are similar to those described for VATS (e.g., uncontrollable bleeding, extensive adhesions, anatomical reasons, and lymph nodes of complex resection) [ 38 , 42 , 75 77 ]. It should be noted that there are several procedures in which robotic systems may even perform better than VATS.…”
Section: Discussionmentioning
confidence: 91%
“…In a large RATS lobectomy series of 500 cases, Herrera et al reported interesting results: an elective conversion rate of 5%, an emergency conversion rate of 0.6%, and a 30-day mortality of 0.6% [ 42 ]. Most frequent complications were atrial fibrillation (14.2% of cases) and prolonged air leak (9.8% of cases).…”
Section: Methodsmentioning
confidence: 99%
“…Like any new technology, the initial legitimate concerns were focused on safety, as the operating surgeon is physically away from the patient, and achieving oncological outcomes that are comparable to the traditional approaches. The scientific literature over the last 2 decades clearly refuted both concerns, as robotic lung surgery was demonstrated to be safe and to achieve at least similar survival to the open and thoracoscopic [video-assisted thoracoscopic surgery (VATS)] approaches (4,5). Furthermore, the robotic platform allowed many to push the boundaries of minimally invasive surgery and tackle complex lung and chest wall procedures, as well advance stage disease after neoadjuvant treatment (6).…”
mentioning
confidence: 99%